Carbon stock and biomass of Baluno Mangrove Forest ecosystems in West Sulawesi, Indonesia - SUPARJO RAZASLI CARONG; AZIIL ANWAR; YASSER AHMED; NUR INDAH SARI ARBIT; ABD MANNAN; RUSMIDIN RUSMIDIN; TAVIP ANWAR; FIRHAN RIMBAWAN (Society for Indonesian Biodiversity, 2024)
Abstract. Carong SR, Anwar A, Ahmed Y, Arbit NIS, Mannan A, Rusmidin, Anwar T, Rimbawan F. 2024. Carbon stock and biomass of Baluno Mangrove Forest ecosystems in West Sulawesi, Indonesia. Biodiversitas 25: 3067-3074. Global warming, fueled by rising CO2 levels, threatens life on earth. Mangrove ecosystems, with their high CO2 absorption capacity, are crucial in climate mitigation efforts. This study aims to identify the attributes of mangrove biomass, quantify carbon stock, and assess the capacity of above-ground biomass (including trees, saplings, and seedlings) and soil to sequester carbon. Carbon stock measurements were conducted in the Baluno Mangrove Forest conservation area which is under the management of the Yayasan Peduli Pengembangan Masyarakat Desa (YPPMD). The sampling strategy employed was stratified proportionate random sampling. The research area is partitioned into multiple strata of mangrove forest vegetation density. The study area consists of 25 plots, each measuring 20x20 (400 m2 soil samples are collected using a soil core to a certain depth, typically up to 30 cm or more. The samples are then analyzed in a laboratory to determine the organic carbon content. Therefore, the total area covered by the plots is 10,000 m2, which is equivalent to 1 hectare. The Baluno Mangroves have a total biomass of 1,558.15 tons/ha. The species with the highest biomass was Sonneratia sp., with a value of 30.81 tons. Conversely, the species having the lowest biomass was Bruguiera gymnorrhiza, with a value of 0.0625 tons. The Baluno Mangrove area has an average carbon stock of 989.04 tons per hectare, with the potential to absorb 3,629.79 tons of CO2 per hectare. In conclusion, Baluno Mangroves store 58,719.57 metric tons of carbon, with Sonneratia sp. as the largest contributor, emphasizing the vital role of Indonesia's mangroves in global carbon sequestration and climate mitigation.